Device-technological simulation of the magnetosensitive sensor with integrated magnetic concentrator - Stempitsky, V. R.; Dao, Dinh Ha (Technology and design in electronic equipment, 2018)
The paper presents results on research and optimization on the basis of device-technological modeling of the structural and operational characteristics of the magnetosensitive sensor with a disk-shaped integrated magnetic concentrator (IMC). The high magnetic permeability of the IMC material provides a high value of the induction of the magnetic field along its edges, which leads to a significant enhancement of the applied external field. The IMC plays the role of a magnetic amplifier, and also affects the signal-to-noise and signal-to-bias ratios; the magnetic gain depends not only on the size of the IMC, but also on its shape. This research is devoted to the development of a disc-shaped magnetic concentrator integrated into the Hall sensor. The concentrator has a high magnetic flux gain and can be used in 3D magnetic field recording systems. Analysis of the geometric dimensions, deflection angle and the material of the integrated magnetic concentrator influence on the characteristics of a three-dimensional magnetic field sensor showed that the inclusion of a ferromagnetic concentrator in the Hall sensor design provides a significant (up to 10 times) increase in the magnetic flux gain. This makes it possible to use the investigated sensor designs to detect weak magnetic fields (from 0.01 μT to 2 mT). It is shown that a supermindure integrated magnetic disc-shaped concentrator with a diameter of D = 200 μm, a thickness of l = 10 μm and an angle of deflection of θ = 60° provides a magnetic flux gain G = 10.81 with a maximum external magnetic field of B0 = 120 mT. The obtained results indicate the prospects of using the proposed constructive solution for the practical manufacture of three-dimensional sensors of weak magnetic fields with a magnetic sensitivity up to 3026 V/(A·T) along the sensor surface. The type of sensor devices studied extends the scope of Hall sensors as an elemental base of medical equipment, equipment for magneto-resonant imaging (MRI), and also in instruments for geological and geodetic research.